Resilience of families with the elderly amid the COVID-19 pandemic: lesson learned from two tourism villages in Yogyakarta, Indonesia - Aswatini Anaf; Sri Sunarti Purwaningsih; Mita Noveria; Dewi Harfina; Destha Titi Raharjana; Dian Wahyu Utami (Cogent Social Sciences, 2024)
AbstractThe COVID-19 pandemic is affecting family members of all age groups in tourism villages in the Yogyakarta Special Region (Daerah Istimewa Yogyakarta – DI Yogyakarta), Indonesia, due to the interruption of tourism activities. This study used a qualitative approach to adapt the theoretical framework of the Family Resilience Model (FRM) by exploring and comprehending the mechanisms through which families with elderly members, navigated the challenges. The result showed that the elderly provided some services to tourists and donated assets during the pandemic to support the family economy. The socio-cultural values of society and respect for the role of the elderly also contributed to the survival of the families. Moreover, the study contributed to understanding the maintenance of family resilience during the pandemic. This could be a lesson to develop assistance programs for the community and the elderly in using their potential.